Evaluation of tourism in the Erdőspuszták sub-region - Suta, Éva (Acta Agraria Debreceniensis, 2006)
The Erdőspuszták sub-region established an Association of Local Municipalities in 1992, 10 settlements of which set up the Erdőspuszták Association in 1995, as a voluntary organization. One third of the settlements in Hajdú-Bihar county are handicapped from an economic or infrastructural point of view.Tourism has become the most dynamically developing industrial sector. Unfortunately, in Hungary and, especially, in the eastern region, this way of earning a living is still in its infancy. Nevertheless, these areas possess such untouched natural values, cultural monuments and unexploited possibilities which could attract tourists.In my study, the problem is examined from two aspects. First, interviews with mayors are included, consisting of three questions. The leaders of the settlements were first asked about the impact of EU accession, then the most important development plans were mapped and finally the local tourism plans were investigated. Second, I have made an evaluation of each settlement which reviews the infrastructural and environmental conditions, the accommodation and boarding possibilities offered the different tourist attractions and leisure possibilities.The development of tourism can be an obvious solution to this problem. The toots of tourism entails the creation of job opportunities, the development of infrastructure, the enhancement of living conditions. It has a diverse effect and it contributes to the improvement of living standards in rural areas.Regarding tourism, it can be stated that each settlement has its own image and value, which the citizens are proud of. It has been realized that collaboration between the settlements could greatly contribute to the development of a tourist programme of several days length, as a result of which the guests would spend more time in the region, which would be beneficial to everybody. My suggestion is that the settlements should work out a plan for the development of tourism jointly, in which they would determine the targets, describe the specific development plans and tasks and elaborate the ideas for the different investments.